Size Matters: The CAG Repeat Length of the Androgen Receptor Gene, Testosterone, and Male Adolescent Depression Severity - Hirtz, Raphael; Libuda, Lars; Hinney, Anke; Föcker, Manuel; Bühlmeier, Judith; Holterhus, Paul-Martin; Kulle, Alexandra; Kiewert, Cordula; Hebebrand, Johannes; Grasemann, Corinna (Frontiers in Psychiatry, 2021)
There is a distinct increase in the prevalence of depression with the onset of puberty. The role of peripubertal testosterone levels in boys in this context is insufficiently understood and may be modulated by a functional polymorphism of the androgen receptor gene (AR), a variable number of CAG repeats. Moreover, there is preliminary evidence that the relationship between testosterone, CAG repeat length, and the severity of depressive symptoms may differ between subclinical and overt depression, but this has neither been studied in a clinical sample of adolescents with depression nor compared between subclinical and overt depression in an adequately powered study. To investigate the relationship between free testosterone, CAG repeat length of the AR, depression status (subclinical vs. overt), and the severity of depressive symptoms, 118 boys treated as in- or daycare patients at a single psychiatric hospital were studied. Of these, 73 boys had at least mild depressive symptoms according to the Beck Depression Inventory-II (BDI-II > 13). Higher-order moderation analysis in the multiple regression framework revealed a constant relationship between free testosterone and depression severity irrespective of the number of CAG repeats in adolescents with a BDI-II score ≤ 13. In adolescents with a BDI-II score > 13, however, there was a significant negative relationship between free testosterone and BDI-II score in patients with less than 19 CAG repeats and a significant positive relationship regarding free testosterone and BDI-II score in those with more than 28 CAG repeats, even when considering important covariates. These results suggest that the effects of testosterone on mood in male adolescents with depression depend on the genetic make-up of the AR as well as on depression status. This complex relationship should be considered by future studies addressing mental health issues against an endocrine background and may, moreover, contribute to tailored treatment concepts in psychiatric medicine, especially in adults.